Association between serum Chlamydia trachomatis antibody levels and infertility among reproductive-aged women in the U.S. - Peiyi Li; Zhiyun Chen (Frontiers Media S.A., 2023)
IntroductionChlamydia trachomatis infection, the most prevalent sexually transmitted bacterial infection worldwide, is a significant cause of infertility. Many countries have introduced the widespread use of serologic assays for IgG seropositivity to chlamydial plasmid gene product 3 (Pgp3). However, data on the association between the level of Pgp3-IgG in the multiplex bead array assay (Pgp3AbMBA) and female infertility are still scarce.MethodsThis cross-sectional analysis included 1,425 women from the National Health and Nutrition Examination Survey (NHANES) from 2013 to 2016.ResultsIn the fully adjusted logistic regression model, each standard deviation increments of Pgp3AbMBA (SD = 17,079.63) led to a 28% increase in the risk of infertility. The relationship remained consistent in women who had been pregnant and women who gave birth. Smooth curve fitting revealed that the association was linear across the entire range of Pgp3AbMBA. Subgroup analysis suggested that the association was significantly stronger in women who had ever used marijuana and lived in poverty.ConclusionsThis study revealed a linear and independent association between the level of Pgp3AbMBA and self-reported infertility in U.S. women. Furthermore, we found that women who had ever used marijuana and lived in poverty were at the highest risk of infertility upon chlamydial infection.